2015
DOI: 10.1016/j.jcis.2015.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of the hydrothermal reduction of palladium on the Tobacco mosaic virus

Abstract: West Lafayette, Indiana ii I dedicate this thesis to my goddaughter, Erinayo Obadina.iii ACKNOWLEDGEMENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Similar to the observations here, His, Asn, and Arg residues of synthetic peptides effectively served as nucleation and stabilizing agents to obtain Pd nanoparticles [36]. Several reports have shown the need for site-directed mutations to insert Cys residues in TMV, providing active sites for the adsorption and reduction of Pd(II) ions and other metal precursors [9,15]. However, wild-type TMV has also proved to be able to stabilize these precursor ions, suggesting that other amino acid residues are involved [9].…”
Section: Molecular Binding Simulation Vp6-pd(ii)supporting
confidence: 80%
See 2 more Smart Citations
“…Similar to the observations here, His, Asn, and Arg residues of synthetic peptides effectively served as nucleation and stabilizing agents to obtain Pd nanoparticles [36]. Several reports have shown the need for site-directed mutations to insert Cys residues in TMV, providing active sites for the adsorption and reduction of Pd(II) ions and other metal precursors [9,15]. However, wild-type TMV has also proved to be able to stabilize these precursor ions, suggesting that other amino acid residues are involved [9].…”
Section: Molecular Binding Simulation Vp6-pd(ii)supporting
confidence: 80%
“…VP6 self-assembles into tubes with a diameter of 75 nm in the pH range of 5.5-7.0, and may support divalent cations up to 200 mM, keeping its macrostructural arrangement [37]. Several reports have shown the need for site-directed mutations to insert Cys residues in TMV, providing active sites for the adsorption and reduction of Pd(II) ions and other metal precursors [9,15]. However, wild-type TMV has also proved to be able to stabilize these precursor ions, suggesting that other amino acid residues are involved [9].…”
Section: Molecular Binding Simulation Vp6-pd(ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a system with much higher Pd concentration, salt build up will increase the ionic strength of the solution and could initiate this Cldriven inhibition even before all of the Pd has reduced. This observation was made in the entryway XAS study performed by Adigun et al 44 in which a much fast reduction was followed by a slower reduction after an initial layer of Pd had grown on the biotemplate surface. This observation about the effect of salt concentration during the mineralization process is also particularly important in view of accessing the future possibility of halide controlled nanocrystal growth in these systems.…”
Section: Resultsmentioning
confidence: 85%
“…Time-resolved XANES spectra were used to obtain the ratio of oxidation states of palladium i.e. Pd (2+) : Pd (0) at different times during synthesis as was previously described by Adigun et al 44 Results from these are shown in Figure 2 Results show that the kinetic constant decreased to zero when a new coating cycle was performed without the removal of ionic products (Figure 3(a)). The opposite observation was made for the mineralization of washed particles i.e.…”
Section: Resultsmentioning
confidence: 99%